2023
DOI: 10.1073/pnas.2214171120
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the nociceptin/orphanin-FQ receptor promotes NREM sleep and EEG slow wave activity

Abstract: Sleep/wake control involves several neurotransmitter and neuromodulatory systems yet the coordination of the behavioral and physiological processes underlying sleep is incompletely understood. Previous studies have suggested that activation of the Nociceptin/orphanin FQ (N/OFQ) receptor (NOPR) reduces locomotor activity and produces a sedation-like effect in rodents. In the present study, we systematically evaluated the efficacy of two NOPR agonists, Ro64-6198 and SR16835, on sleep/wake in rats, mice, and Cyno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…N/OFQ and its receptor NOPR have been implicated in neuromodulation of a wide variety of essential behavioral processes including stress, aversion, motivation, reward seeking, and feeding. 22,23,27,51,52,53,54,55,56 We have previously identified a role for VTA N/OFQ signaling in reward-related and aversive behavior, and using GCaMP found that pnVTA PNOC neurons activity is suppressed during sucrose consumption. 22 There-fore, we injected WT mice with AAV-DJ-hSyn-NOPLight in the VTA, implanted optical fibres above the injection site, and secured stainless steel rings to allow for head-fixed fibre photometry recording of NOP-Light during sucrose consumption ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…N/OFQ and its receptor NOPR have been implicated in neuromodulation of a wide variety of essential behavioral processes including stress, aversion, motivation, reward seeking, and feeding. 22,23,27,51,52,53,54,55,56 We have previously identified a role for VTA N/OFQ signaling in reward-related and aversive behavior, and using GCaMP found that pnVTA PNOC neurons activity is suppressed during sucrose consumption. 22 There-fore, we injected WT mice with AAV-DJ-hSyn-NOPLight in the VTA, implanted optical fibres above the injection site, and secured stainless steel rings to allow for head-fixed fibre photometry recording of NOP-Light during sucrose consumption ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These data also provide the ability to align neuronal activity measured either by calcium dynamics or electrophysiology with neuropeptide release during freely-moving behaviorial epochs. Given the recent discoveries that PNOC and NOPR are important for motivation, feeding, and sleep induction 22,23,[50][51][52][53] , understanding the dynamic properties of this opioid peptide system is now of even greater importance as this receptor is now considered a major target for insomnia, addiction, and depression 49,61,62 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data also provide the ability to align neuronal activity measured either by calcium dynamics or electrophysiology with neuropeptide release during freely moving behavioral epochs. Given the recent discoveries that PNOC and NOPR are important for motivation, feeding, and sleep induction 22 , 23 , 50 53 , understanding the dynamic properties of this opioid peptide system is now of even greater importance as this receptor is now considered a major target for insomnia, addiction, and depression 49 , 60 , 61 .…”
Section: Discussionmentioning
confidence: 99%